ON THE QUESTION OF THE EVACUATION OF CHILDREN FROM CHILDREN'S PLAYROOMS OF SHOPPING MALLS - Dmitry Vjacheslavovich Tekushin; Grigory Ivanovich Rudchenko (Современная наука и инновации)
The Volgograd State Architectural and Construction University (VolgSACU) actively explores the process of people's evacuation from buildings of different functionality during emergency situations. This article is devoted to studying the behavior of shopping malls personnel in case of fire. Including to application techniques they developed - data - gathering interviews using computer video presentations.